2016
DOI: 10.3141/2570-02
|View full text |Cite
|
Sign up to set email alerts
|

Emissions Modeling with MOVES and EMFAC to Assess the Potential for a Transportation Project to Create Particulate Matter Hot Spots

Abstract: In particulate matter (PM) nonattainment and maintenance areas, quantitative hot-spot analyses are required to assess air quality impacts of transportation projects that are identified as projects of local air quality concern (POAQC). In its 2006 rulemaking, the U.S. Environmental Protection Agency identified sample projects that would likely be POAQCs, including a new highway project with annual average daily traffic (AADT) greater than 125,000 and at least 8% diesel truck traffic. The objective of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…However, MOVES exhaust emissions estimates for 2006 were about 70% higher than the EMFAC estimates. On the other hand, EMFAC brake wear estimates were 2.5 times higher than the MOVES estimates [12].…”
Section: Classical Regression Models For Particulate Mattermentioning
confidence: 70%
See 2 more Smart Citations
“…However, MOVES exhaust emissions estimates for 2006 were about 70% higher than the EMFAC estimates. On the other hand, EMFAC brake wear estimates were 2.5 times higher than the MOVES estimates [12].…”
Section: Classical Regression Models For Particulate Mattermentioning
confidence: 70%
“…To assess air quality impacts of transportation projects and determine which projects should be identified as a Project of Air Quality Concern (POAQC), Reid et al (2017) used both the MOVES and the Emission Factors model (EMFAC) to quantify PM10 and PM2.5 emissions in an analysis conducted for the year 2006. Their goal was to evaluate the impact of fleet turn-over and truck use percentages on future project-level emissions [12]. Comparing the two models, they concluded that tire wear and re-entrained road dust emissions from both models were roughly equal.…”
Section: Classical Regression Models For Particulate Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…To assess air quality impacts of transportation projects and determine which projects should be identified as a Project of Air Quality Concern (POAQC), Reid et al (2017) used both the MOVES and the Emission Factors model (EMFAC) to quantify PM10 and PM2.5 emissions in an analysis conducted for the year 2006. Their goal was to evaluate the impact of fleet turn-over and truck use percentages on future project-level emissions [13]. Comparing the two models, they concluded that tire wear and re-entrained road dust emissions from both models were roughly equal.…”
Section: Classical Regression Models For Particulate Mattermentioning
confidence: 99%
“…Additionally, it builds upon the studies mentioned above to develop a working model of particulate matter for California. In particular, monthly PM2.5 data are generated [13], monthly observed meteorological data are acquired [14,19], spatial analysis is utilized to improve low data resolution [16], and eventually, the ANN approach is used to develop an accurate model for particulate matter spatial distribution based on the meteorological variables [15,17,18]. The work's novelty is an in-depth study of the impact of spatial resolution and the use of model-generated particulate matter.…”
Section: Ann Models For Particulate Mattermentioning
confidence: 99%